The factors contribute to the customers' acceptance towards 'Talk Around a Clock' call plan introduced by Telekom / Raja Shahrizal Raja Ahmad Shafiei - Raja Ahmad Shafiei, Raja Shahrizal (Faculty of Business and Management, 2005)
The purpose of the study is to identify the factors could be contributed to the customers' acceptance towards 'Talk Around a Clock' call plan introduced by Telekom. The research is focus on four major factors which are demographic factors (gender, age, race, marital status, education, residential area income), marketing efforts of the company which is rely on advertisements, usage of telephone (telephone bill exceed RM65) and benefits of the call plan. Based on the problem statement, this research is conducted to achieve these objective; (1) To determine whether demographic factors have positively influence the customers that subscribe the 'Talk Around a Clock' call plan, (2) To identify which one of the advertisements (TV, newspaper, radio) used by Telekom influence customers to subscribe the 'Talk Around a Clock' call plan., (3) To know whether the monthly telephone bill of customers have significant relationship with the customer’s acceptance towards call plan and (4) To examine whether there is significant relationship between the benefits of the call plan and the acceptance towards the call plan. From the findings, not all the demographic factors have positive relationship with the acceptance of customers towards the call plan. Only age and residential area of the customers have positive relationship towards the customers' acceptance towards the call plan. Television is the advertisement media used by the company that has influence most subscribers to subscribe the call plan. The average monthly telephone bill does have significant relationship with the acceptance of customers towards the call plan. The higher the telephone bill of the customers is the higher probability that they would subscribe the call plan. Moreover, the customers are likely to be attracted to the benefits offered from the call plan.